2013
DOI: 10.1074/jbc.m112.440602
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of GTP-binding Protein (Gαs) Expression in Human Myometrial Cells

Abstract: Background:The GTP-binding protein G␣ s facilitates myometrial quiescence during pregnancy. Results: TNF overcomes trichostatin A (TSA)-induced myometrial relaxation. This is due to changes in levels of CBP and acetylated H4K8 within the G␣ s promoter. Conclusion: Promoter acetylation is important in governing expression of G␣ s . Significance: TSA-induced myometrial relaxation can be overcome by TNF through repression of G␣ s promoter activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…In our previous studies, we have reported differential effects of both TNF and TSA on signaling pathways in primary myometrial myocytes (Chapman et al, 2005 ; Webster et al, 2013 ). In the present study we sought to determine if such compounds could also influence expression of the MaxiK mRNA.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…In our previous studies, we have reported differential effects of both TNF and TSA on signaling pathways in primary myometrial myocytes (Chapman et al, 2005 ; Webster et al, 2013 ). In the present study we sought to determine if such compounds could also influence expression of the MaxiK mRNA.…”
Section: Resultsmentioning
confidence: 95%
“…We and others have previously demonstrated that external agents such as TNF (potent pro-inflammatory cytokine) can induce myometrial contractility while other compounds, namely trichostatin-A (TSA), can promote myometrial relaxation in isolated human smooth muscle strips (Lu et al, 1999 ; Moynihan et al, 2008 ; Webster et al, 2013 ). While the exact means by which this process occurred could not be elucidated, that study also demonstrated that TSA caused an up-regulation of the GTP-binding protein, Gαs, while TNF had the reciprocal function and repressed the Gαs promoter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genes examined in this study are listed in Table 2. The approach to gene selection for this panel was multifactorial: a number of genes encoding for proteins associated with the physiological events of uterine contraction, cervical dilation and membrane rupture that occur during human labor, termed labor associated genes, were selected (41); also, for comparison, a collection of genes encoding for G-proteins involved in maintaining uterine quiescence (42). A number of pro inflammatory genes, including genes encoding for proteins in the NFκB pathway (16), and genes involved in the production of prostaglandins (18) were chosen to aid understanding of the potential mechanism of action of inhibitors used in this study.…”
Section: Resultsmentioning
confidence: 99%